High-dimensional comparison of monocytes and T cells in post-COVID and idiopathic pulmonary fibrosis - Bingham, Grace C.; Muehling, Lyndsey M.; Li, Chaofan; Huang, Yong; Ma, Shwu-Fan; Abebayehu, Daniel; Noth, Imre; Sun, Jie; Woodfolk, Judith A.; Barker, Thomas H.; Bonham, Catherine A. (Frontiers in Immunology, 2024)
Up to 30% of hospitalized COVID-19 patients experience persistent sequelae, including pulmonary fibrosis (PF). We examined COVID-19 survivors with impaired lung function and imaging worrisome for developing PF and found within six months, symptoms, restriction and PF improved in some (Early-Resolving COVID-PF), but persisted in others (Late-Resolving COVID-PF). To evaluate immune mechanisms associated with recovery versus persistent PF, we performed single-cell RNA-sequencing and multiplex immunostaining on peripheral blood mononuclear cells from patients with Early-and Late-Resolving COVID-PF and compared them to age-matched controls without respiratory disease. Our analysis showed circulating monocytes were significantly reduced in Late-Resolving COVID-PF patients compared to Early-Resolving COVID-PF and non-diseased controls. Monocyte abundance correlated with pulmonary function forced vital capacity and diffusion capacity. Differential expression analysis revealed MHC-II class molecules were upregulated on the CD8 T cells of Late-Resolving COVID-PF patients but downregulated in monocytes. To determine whether these immune signatures resembled other interstitial lung diseases, we analyzed samples from Idiopathic Pulmonary Fibrosis (IPF) patients. IPF patients had a similar marked decrease in monocyte HLA-DR protein expression compared to Late-Resolving COVID-PF patients. Our findings indicate decreased circulating monocytes is associates with decreased lung function and uniquely distinguishes Late-Resolving COVID-PF from Early-Resolving COVID-PF, IPF, and non-diseased controls.